Positive and Negative Feedback Regulation in the Production and Secretion of Insulin from INS-1 Cells by Testosterone - Cui, Y.; Ma, J.; Shi, Y.; Huan, Q.; Guo, H.; Zhao, Y.; Chen, Z.-J. (Hormone and Metabolic Research, 2011)
Type 2 diabetes is often developed in genetically predisposed subjects combined with sedentary life style or environmental factors. In women with polycystic ovary syndrome, hyperandrogenism is often accompanied with hyperinsulinemia and insulin resistance. Further, some studies have found associations of hyperandrogenemia with β-cell dysfunction and type 2 diabetes. We therefore tested the impairment effect of testosterone on glucose-stimulated insulin secretion in INS-1 cells. INS-1 cells were treated with different concentrations of testosterone and examined at different time points. In contrast to control, excess testosterone treatment for 48 h could promote glucose-stimulated insulin secretion and enhance pancreatic/duodenal homeobox-1 and glucose transporter-2 mRNA expression up to 2-fold. Alternatively, long-time and high-concentration testosterone treatment significantly impaired glucose-stimulated insulin secretion and insulin mRNA levels and promoted malondialdehyde content. Androgen receptor antagonist flutamide could partly attenuate glucose-stimulated insulin secretion. These results indicate that direct in vitro exposure of INS-1 cells to testosterone had both concentration- and time-dependent effects on glucose-stimulated insulin secretion, gene expression, and oxidative stress. These findings showed to some extent that excess circulation of testosterone might impair β-cell function, and further contribute to the etiology of insulin resistance in polycystic ovary syndrome.
Keywords: testosterone; INS-1 cells; GSIS